A sociology of caravans - Beilharz, Peter; Supski, S. (Sage Publications Ltd., 2017)
Why do caravans matter? Australians, like others, holiday in them, travel in them, cook, eat, drink, play, sleep and have sex in them. They also live in them, often involuntarily. Caravans have a longer history than this, however caravan life has almost no presence in existing historical or cultural sociology scholarship. Our immediate interest is in caravans in Australia, modernity and mobility. Some broader interest is apparent. Theoretical arguments about mobility on a global scale have been developed by Bauman and Urry. Sociologists like Jasper have connected mobility, masculinity and automobility in Restless Nation. The sociologist and writer Marina Lewycka has used caravans as the locus of everyday life study in her novel Two Caravans. In this paper we background some of these broader issues, and offer a case study of postwar caravan manufacturing. This paper anticipates a larger possible research project in these fields. We anticipate this project raising themes like freedom, mobility, escape, utopia; images of domesticity on wheels, décor and design, materials, technology, DIY production and Fordism; caravan parks as homes and as itinerant and long-term accommodation. These themes and images are also necessarily interwoven with class, gender, sex and age. We are interested in the possibilities of using the caravan as a carrier for making sense of postwar Australia.